Rituximab to treat prolidase deficiency due to a novel pathogenic copy number variation in PEPD - Torsten Witte; Georgios Sogkas; Natalia Dubrowinskaja; Faranaz Atschekzei; Theresa Graalmann; Mykola Fedchenko; Abdulwahab Elsayed; Felix C Ringshausen (RMD Open, 2023)
Prolidase deficiency (PD) is a rare autosomal recessive inborn error of immunity caused by biallelic homozygous or compound heterozygous loss-of-function mutations in PEPD, the gene that encodes prolidase. PD typically manifests with variable dysmorphic features, chronic cutaneous ulcers, recurrent infections and autoimmune features, including systemic lupus erythematosus. So far, there is no consensus regarding treatment of PD and its autoimmune manifestations. Here, we present a 28-year-old female patient with PD due to a novel homozygous intragenic deletion in PEPD, diagnosed at the age of 6 years and 7 months with an undifferentiated connective tissue disease that, apart from its very early onset, would be consistent with the diagnosis of Sjögren’s syndrome. Steroids and diverse conventional synthetic disease-modifying antirheumatic drugs failed to control PD-associated vasculitis and mucocutaneous ulcerations and led to infectious complications, including cytomegalovirus colitis. Introduction of rituximab (RTX) treatment in this patient led to sustained recession of mucocutaneous ulceration, enabling tapering of steroids. High interleukin-1β (IL-1β) production by this patient’s monocytes, together with the detection of both IL-1β and interleukin-18 (IL-18) in her serum, suggest enhanced inflammasome activation in PD, whereas the therapeutic efficacy of RTX implies a role for CD20 positive B cells in the complex immunopathogenesis of PD.